A Critical Discourse Analysis of Bilawal Bhutto Zardari’s Speech at USIP - Ayesha Akram; Dr. Farooq Ahmad, (Dialogue Social Science Review (DSSR), 2025)
This paper critically analyzes Bilawal Bhutto Zardari's address at the USIP in Washington, DC. The paper examines Bilawal Bhutto Zardari's rhetorical methods to promote Pakistan's peaceful character and his own political aspirations. The objectives of the study are to identify and analyze the speech's dominant discourses and ideologies, examine the rhetorical devices used to promote Pakistan’s stance on peace, and understand how the speaker uses language to construct and promote his political identity. Fairclough's Critical Discourse Approach (CDA) model which examines language, power, and social context in social realities and discursive systems has been utilized as method of research. The speech skillfully uses language, structure, and historical allusions to illustrate the necessity of democracy in combatting extremism. It shows the speaker's knowledge of religious fanaticism's social, cultural, and political elements. The research found that Bilawal Bhutto Zardari's speech conveyed its message, resonated with the audience, and established him as an authoritative and informed voice on the issue.